Human Height Is Positively Related to Interpersonal Dominance in Dyadic Interactions - Stulp, Gert; Buunk, Abraham P.; Verhulst, Simon; Pollet, Thomas V. (PLOS ONE, 2015)
Across cultures, taller stature is linked to increased social status, but the potential reasons why this should be are unclear. One potential explanation is that taller individuals are more likely to win a dyadic confrontation with a competitor (i.e., they are more dominant), which leads to higher social rank. Although some previous studies have shown that perceptions of status or dominance are related to height, and are therefore consistent with such an explanation, there is surprisingly little research testing whether height actually has any influence on the behavioural outcomes in real-life social interactions. Here, we present three naturalistic observational studies demonstrating that height predicts interpersonal dominance during brief dyadic interactions. Study 1 investigated the likelihood of giving way in a narrow passage (N = 92); Study 2 investigated giving way in a busy shopping street, plus the likelihood of colliding with another individual (N = 1,108); and Study 3 investigated the likelihood of maintaining a linear path while walking, and potentially entering another individual’s personal space (N = 1,056). We conclude that human height is positively related to interpersonal dominance, and may well contribute to the widely observed positive association between height and social status.